An in vitro comparison between the apical sealing abilities of resilon with Epiphany® sealer and gutta-percha with AH plus sealer - Rajan T Lambor; Ida de Noronha de Ataide; Paul Chalakkal; Francis Akkara; Suhail Ahamed Shariff; Kristlee Sabrin Fernandes (Wolters Kluwer Medknow Publications, 2012)
Context: The study assesses the apical sealing ability of two obturating materials (resilon and gutta-percha) with their sealants by means of the dye penetration method using India ink. Aims: To compare the resistance to apical dye penetration between resilon (with Epiphany sealer; Epiphany®, Pentron clinical technologies, USA) and gutta-percha (with AH Plus sealer; Dentsply, Maillefer, Germany). It was hypothesized that there would be no difference between the two groups with regard to apical dye penetration. Settings and design: Hundred mandibular first premolars from individuals aged between 20 to 25 years were selected after their lengths were standardized. Materials and Methods: Instrumentation was performed with NiTi hand protaper files (Dentsply, Maillefer) using EDTA paste and copious irrigation with 2.5% sodium hypochlorite. Experimental group 1 consisted of roots that were treated with Epiphany primer and obturated with resilon (with Epiphany sealer). Experimental group 2 consisted of those obturated with gutta-percha using AH Plus sealer. The samples were immersed in blue India Ink and cleared using 5% nitric acid. Dye penetration was assessed under a stereomicroscope. Statistical analysis: Mann-Whitney U test. Results: Roots obturated with resilon core material and Epiphany sealer exhibited lesser mean apical dye penetration (1.281 mm; SD: 0.742) in comparison to those obturated with gutta-percha and AH plus sealer (2.154 mm; SD: 0.814). The difference was found to be highly significant (P<0.0025). Conclusion: Resilon (with Epiphany sealer) provided better radicular apical sealing in comparison to gutta percha (with AH Plus sealer).